BIRAK-KAZAN 1996 ULUSLARARASI ÇEKİLİŞLİ SİGARAYI BIRAKMA KAMPANYASININ ELAZIĞ İLİ PİLOT ÇALIŞMASININ DEĞERLENDİRİLMESİ - POLAT, S. Aytaç; Sezer, Erol (Cerrahpaşa Medical Journal, 2014)
Background and Design.- This is a follow up study aimed to evaluate the effects of the Smoking Cessation Campaign in Elazığ 1996. A random sample of 1000 participants were drawn randomly from a list of 1299 participants. Number of the individuals in the final list was 978. Most of the questions in the questionnaire were the ones requested by the international Quit and Win campaign coordination center. The study was conducted during may 1997 just one year after the cessation campaign had been launched. Of the individuals in the sample 759 responded. Results.- The participation rates were 2,84% and 0,34% among the smokers in the provincial center and the rest of the Elazığ respectively. The overall participation rate was 1.37%. Of the respondents 83.0% were male, 70.0% were between the ages of 25-44. Most of the respondents had at least a high school degree. And 63.6% of the responders were able to give up smoking during campaign period. Among the main reasons reported by the ones who failed to give up smoking were tobacco withdrawal symptoms, and stress. One year abstinence rate among respondents was 33.9%. (If 176 individuals who did not respond are supposed to have failed to give up, this figure will decrease to 27.0%) Among the respondents 23,7% reported that they had smoked sometimes during the 12 months after quit day but they did not smoke at the time of survey; 7.4% reported that although they had continuously smoked in the last year they did not smoke at the time of the survey; 35.0% reported that they had smoked in the last year and they also continued to smoke at the time of the survey. Conclusion.- The results of the survey shows that launching Quit and Win Campaigns is a worthwhile strategy to curb smoking epidemic.